Raising Legal Awareness: Understanding the Urgency of Trademark Registration in Teluk Sepang Village, Kampung Melayu District, Bengkulu City - Wafiya Wafiya; Ganefi Ganefi (Probono and Community Service Journal, 2023)
This community service program aims to raise awareness among dried fish business operators in Teluk Sepang Village, Kampung Melayu District, Bengkulu City, about the importance of branding in trading businesses. Additionally, it seeks to disseminate information regarding the scope and regulations of the Trademark Law to the community of dried fish business operators in the mentioned village and district. The program involves the dissemination and motivation of dried fish business operators/traders in Teluk Sepang Village, Kampung Melayu District, Bengkulu City. Based on the conducted activity, it was found that the operators lacked awareness of the law, primarily due to reluctance in trademark registration. They cited reasons such as operating in rented premises on a monthly basis and the possibility of relocating their businesses. Moreover, most traders do not have their own kiosks, and they rarely receive guidance from relevant agencies. Through this program, the aim is to motivate dried fish traders to establish their own business brands, thereby enhancing the economic value of their products.